Value Added Analysis and Quality Test of Cassava Crackers (Manihot Esculenta Crantz) in the Household Agroindustry in Cot Glie Aceh Besar District - AR, Chairuni; Makmur, Teuku; Lamona, Asmeri; Ahyar, Zakya; Irmayanti, Irmayanti (International Conference on Multidisciplinary Research, 2020)
In Indonesia, especially in Aceh Province, cassava is often used as raw material for the food industry, so the food is considered crucial in various businessesfood product. The purpose of processing cassava into a food product is to increase the durability of the cassava plant so that the selling price of cassava is more economical. One of the examples of the diversifying processed products from cassava is cassava cracker; and one of the centers of production in Aceh Province. It is located in Cot GlieAceh Besar. The present study aimed to measure the added value and test the quality of cassava crackers produced in Cot Glie District. Particularly, this study aimed to answer the following questions: (1) How is cassava manufactured into cassava crackers?, (2) How is the added value generated from processing cassava into cassava crackers in Cot Glie region?, (3) How is the quality of cassava cracker produced in household agro-industry of Cot Glie Aceh Besar?. The Snowball Sampling method was employed in determining the samples, and value-added analysis the Hayami method was employed. The findings of the research can be concluded as follows: (1) The process of processing cassava into cassava crackers on a household industrial scale in the study area is still relatively simple, (2) The added value generated from processing cassava into cassava crackers on a home industry scale in the study area is also still relatively simple,(3) The quality test of the water content and ash content produced in the business cassava crackers in the household industry scale of the study area has met the standard of SNI 0272-1990, with a maximum water content of 11% and a maximum ash content of 2%.Â Keywords: cassava, crackers, value-added, quality, agroindustryÂ